High-amplitude fast activity in EEG: An early diagnostic marker in children with beta-propeller protein-associated neurodegeneration (BPAN). Issue 9 (September 2020) - Kidokoro, Hiroyuki; Yamamoto, Hiroyuki; Kubota, Tetsuo; Motobayashi, Mitsuo; Miyamoto, Yusaku; Nakata, Tomohiko; Takano, Kyoko; Shiba, Naoko; Okai, Yu; Tanaka, Masaharu; Sakaguchi, Yoko; Maki, Yuki; et al.
Highlights: The early diagnosis of beta-propeller protein-associated neurodegeneration (BPAN) remains challenging. The EEGs of children with BPAN show prominent high-amplitude fast activity as early as 1 year of age. EEG provides an important clue for the early diagnosis of BPAN. Abstract: Objective: The early diagnosis of beta-propeller protein-associated neurodegeneration (BPAN) before distinct brain magnetic resonance imaging (MRI) findings of iron deposition occur remains challenging. This study examined whether children with BPAN have characteristic high-amplitude (>50 μV) fast activity (HAFA) on electroencephalography (EEG). Methods: We conducted a retrospective analysis of EEG performed during childhood in five patients with BPAN. We also examined 143 EEGs from 59 patients with different etiologies, including epilepsy (n = 33), acute encephalopathy (n = 6), neurodevelopmental disorders (n = 5), non-epileptic events (n = 4), and others (n = 11). Trained electroencephalographers reviewed all of the EEGs. When excessive fast activity was observed, the amplitude, frequency, and locality were assessed. Results: All five patients with BPAN underwent initial EEGs at 12–21 months old, and diffuse continuous HAFA (range 20–50 Hz) was observed on both awake and sleep EEGs. In the awake records, there was no clear posterior dominant rhythm in 4 of the 5 patients. Although 28% of the 143 EEGs had continuous excessive fast activity, mainly in the sleep records, only two (1.4%) exhibited HAFA when asleep, and their awake EEGs had clear posterior dominant rhythm. Conclusions: The EEGs of children with BPAN showed diffuse HAFA continuously when both awake and asleep, which is uncommon in children with other etiologies. Significance: This study provides an important clue for the early diagnosis of BPAN.